2020
DOI: 10.1787/c5dc0c50-en
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality

Abstract: systems/health-working-papers.htm OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed are those of the author(s). Working Papers describe preliminary results or research in progress by the author(s) and are published to stimulate discussion on a broad range of issues on which the OECD works. Comments on Working Papers are welcomed, and may be sent to health.contact@oecd.org. This series is designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 3 publications
1
9
0
1
Order By: Relevance
“…It should be noted that we see that mortality in January and February 2020, before the COVID-19 pandemic, was lower than previous years, similar to that noted in many European countries, due to less severe and earlier seasonal diseases such as influenza in the winter of 2019/2020 [6]. It is important to compare only March to November mortality when checking for excess mortality from COVID-19, when COVID deaths began in Israel.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…It should be noted that we see that mortality in January and February 2020, before the COVID-19 pandemic, was lower than previous years, similar to that noted in many European countries, due to less severe and earlier seasonal diseases such as influenza in the winter of 2019/2020 [6]. It is important to compare only March to November mortality when checking for excess mortality from COVID-19, when COVID deaths began in Israel.…”
Section: Discussionsupporting
confidence: 58%
“…The OECD [6] used as a comparative measure the maximum aggregate excess mortality for each country over a 10-week period in the first wave (i.e. choosing the 10week period for which total excess mortality was highest).…”
Section: Excess Mortality By Weekmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of the U.S., other studies have found increases in excess mortality of 61 percent in Spain, 56 percent in the United Kingdom, and five percent or lower in Germany, Denmark, and Norway (Morgan et al 2020). Other work finds increases in excess deaths in England, Wales, France, Italy, Netherlands, and Portugal (FĂ©lix-Cardoso et al 2020).…”
Section: Literature Reviewmentioning
confidence: 97%
“…This approach was initially met with criticism, both at the national and the international levels. However, by the end of April, international comparisons revealed that Belgium had a particularly exhaustive approach of reporting COVID-19 deaths [ 6 , 9 , 10 ]. Moreover, an excellent correlation between the all-cause excess mortality and the reported COVID-19 deaths could be shown on a daily basis [ 11 - 15 ].…”
Section: Introductionmentioning
confidence: 99%